Ascorbic Acid Regulates the Immunity, Anti-Oxidation and Apoptosis in Abalone Haliotis discus hannai Ino - Kai Luo; Xinxin Li; Liu Wang; Wanxiu Rao; Yang Wu; Yue Liu; Mingzhu Pan; Dong Huang; Wenbing Zhang; Kangsen Mai (MDPI AG, 2021)
The present study was conducted to investigate the roles of ascorbic acid (AA) in immune response, anti-oxidation and apoptosis in abalone (Haliotis discus hannai Ino). Seven semi-purified diets with graded levels of AA (0, 50, 100, 200, 500, 1000 and 5000 mg/kg) were fed to abalone (initial weight: 12.01 ± 0.001 g, initial shell length: 48.44 ± 0.069 mm) for 100 days. The survival, weight gain rate and daily increment in shell length were not affected by dietary AA. The AA content in the gill, muscle and digestive glands of abalone was significantly increased by dietary AA. In terms of immunity, dietary AA significantly improved the total hemocyte count, respiratory burst and phagocytic activity in hemolymph, and lysozyme activity in cell-free hemolymph (CFH). In the digestive gland, the TLR-MyD88-dependent and TLR-MyD88-independent signaling pathways were suppressed by dietary AA supplementation. The mRNA levels of β-defensin and arginase-I in the digestive gland were significantly increased by dietary AA. In the gill, only the TLR-MyD88-dependent signaling pathway was depressed by dietary AA to reduce inflammation in abalone. The level of mytimacin 6 in the gill was significantly upregulated by dietary AA. After Vibrio parahaemolyticus infection, the TLR signaling pathway in the digestive gland was suppressed by dietary AA, which reduced inflammation in the abalone. In terms of anti-oxidation, superoxide dismutase, glutathione peroxidase and catalase activities, as well as total anti-oxidative capacity and reduced glutathione content in CFH, were all significantly upregulated. The malondialdehyde content was significantly downregulated by dietary AA. The anti-oxidative capacity was improved by triggering the Keap1-Nrf2 pathway in abalone. In terms of apoptosis, dietary AA could enhance the anti-apoptosis ability via the JNK-Bcl-2/Bax signaling cascade in abalone. To conclude, dietary AA was involved in regulating immunity, anti-oxidation and apoptosis in abalone.